2013
DOI: 10.1177/1352458513498829
|View full text |Cite
|
Sign up to set email alerts
|

Combining HLA-DR risk alleles and anti-Epstein-Barr virus antibody profiles to stratify multiple sclerosis risk

Abstract: The ability to discriminate MS cases and controls can be substantially enhanced by including anti-EBV serology as well as HLA-DR risk profiles. These findings support the relevance of EBV-specific immunity in MS pathogenesis, and implicate both HLA-dependent and HLA-independent immune responses against EBNA-1 as prominent disease risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…IgG reactive with EBV viral capsid antigen (EBV-VCA) was detected using a commercial kit (DiaSorin, Vercelli, Italy). Plasma was diluted 1 : 1075 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…IgG reactive with EBV viral capsid antigen (EBV-VCA) was detected using a commercial kit (DiaSorin, Vercelli, Italy). Plasma was diluted 1 : 1075 [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The risk of MS increases positively with levels of circulating anti-EBNA antibodies (Ascherio et al 2001; DeLorenze et al 2006; Levin et al 2005; Sundstrom et al 2004.) The ability to discriminate MS cases and controls was substantially enhanced by the inclusion of quantitative measures of the anti-EBNA-1 response to EBV infection (Strautins et al 2014). Interestingly, the strong genetic association of MS with particular human leukocyte antigen (HLA) alleles primarily reflects the association with anti-EBV responses (Rubicz et al 2013).…”
Section: Clinical Manifestations Of Primary Ebv Infectionmentioning
confidence: 99%
“…Both serological [ 27 , 31 , 32 ] and CD4 T cell responses [ 33 ] directed against EBNA-1 have been associated with multiple sclerosis, with further evidence that EBNA-1-specific antibodies differentiate disease-discordant identical twins [ 34 ]. Several groups have demonstrated higher EBV seroprevalence in MS patients compared to controls and it has further been demonstrated that EBV infection late in life, in particular if manifested as infectious mononucleosis, increases a person’s MS risk [ 27 , 35 , 36 ]. A recent study has also explored the use of Epstein-Barr virus-specific adoptive immunotherapy for progressive multiple sclerosis, with promising preliminary results [ 37 ].…”
Section: Introductionmentioning
confidence: 99%